Agro-physiological and transcriptome profiling reveal key genes associated with potato tuberization under different nitrogen regimes in aeroponics - Rasna Zinta; Jagesh Kumar Tiwari; Tanuja Buckseth; Umesh Goutam; Rajesh Kumar Singh; Ajay Kumar Thakur; Vinod Kumar; Shwetank Singh; Manoj Kumar (PLoS ONE, 2025)
Nitrogen (N) is a crucial nutrient for the growth and development of potatoes. However, excessive use of nitrogen fertilizers can have detrimental effects on human health, aquatic ecosystems, and the environment. Therefore, understanding the genes involved in nitrogen metabolism is essential for developing future strategies to improve nitrogen use efficiency (NUE) in plants. This study aimed to identify genes associated with high tuber yield in two contrasting potato varieties Kufri Jyoti (N inefficient) and Kufri Pukhraj (N efficient) grown under low and high nitrogen regimes using an aeroponics system. Both varieties were grown in aeroponics with two nitrogen doses (low N: 0.5 mM N; high N: 5 mM N) using a completely randomized design (CRD) with three replications over two years. The phenotypic results confirmed that Kufri Pukhraj was more nitrogen use efficient compared to Kufri Jyoti, particularly under low nitrogen conditions. Additionally, transcriptome analysis produced high-quality data ( ≥ Q20), ranging from 4.35 to 5.46 Gb per sample. Statistically significant genes (p ≤  0.05) were identified based on the reference potato genome. Differentially expressed genes (DEGs) were categorized as either up-regulated or down-regulated in leaf and tuber tissues. Transcriptome profiling of both tuber and leaf tissues revealed genes associated with traits contributing to high tuber yield under both high and low nitrogen conditions. The DEGs were further characterized through gene ontology (GO) annotation and KEGG pathway analysis. Selected genes were validated through real-time quantitative polymerase chain reaction (RT-qPCR) analysis. In summary, several genes were identified as being involved in high tuber yield component traits in potatoes under different nitrogen conditions. These included glutaredoxin, transcription factors (BTB/POZ, AP2/ERF, and MYB), nitrate transporter, aquaporin TIP1;3, glutamine synthetase, aminotransferase, GDSL esterase/lipase, sucrose synthase, UDP-glycosyltransferases, osmotin, xyloglucan endotransglucosylase/hydrolase, and laccases. Additionally, we identified overexpressed genes including cysteine protease inhibitor 1, miraculin, sterol desaturase, and pectinesterase in Kufri Pukhraj under low N stress. Our study highlights these genes’ roles in enhancing tuber yield in potatoes cultivated under both high and low nitrogen in aeroponics.